2017
DOI: 10.1371/journal.pone.0169688
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pulp and Na-Bentonite Amendments on the Mobility of Trace Elements, Soil Enzymes Activity and Microbial Parameters under Ex Situ Aided Phytostabilization

Abstract: The objective of this study was to explore the potential use of pulp (by-product) from coffee processing and Na-bentonite (commercial product) for minimizing the environmental risk of Zn, Pb and Cd in soil collected from a former mine and zinc-lead smelter. The effects of soil amendments on the physicochemical properties of soil, the structural and functional diversity of the soil microbiome as well as soil enzymes were investigated. Moreover, biomass of Festuca arundinacea Schreb. (cultivar Asterix) and the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…The addition of bentonite may improve phytoremediation outcomes since it reduces both the soluble and bioavailable fractions of Ni due to the capacity of this mineral to adsorb the metal in its external and internal sites, as described by other authors [75,80,81]. As reported in previous work [67], the competition of bentonite adsorption sites with Ni adsorbed on organic matter and the stabilisation of the metal in internal adsorption sites of bentonite could reduce the available concentration of Ni in lime (Figure 1b).…”
Section: Greenhouse Experimentssupporting
confidence: 63%
“…The addition of bentonite may improve phytoremediation outcomes since it reduces both the soluble and bioavailable fractions of Ni due to the capacity of this mineral to adsorb the metal in its external and internal sites, as described by other authors [75,80,81]. As reported in previous work [67], the competition of bentonite adsorption sites with Ni adsorbed on organic matter and the stabilisation of the metal in internal adsorption sites of bentonite could reduce the available concentration of Ni in lime (Figure 1b).…”
Section: Greenhouse Experimentssupporting
confidence: 63%
“…In these cases, increased growth (Senthilkumar et al, 2015), (Osorio et al, 2002) and production (Pagán-Roig et al, 2016), (Senthilkumar et al, 2015) of treated plants, increased biomass (Pagan-Roig et al, 2016;Pagán-Roig et al, 2016;Wasilkowski et al, 2017), increased humic acids and polymerization (Pagán-Roig et al, 2016) have been reported. There was overall improvement in soil fertility and quality (Cervantes et al, 2014(Cervantes et al, , 2015aBetancourt et al, 2016;Wasilkowski et al, 2017), as well as efficient (Pagán-Roig et al, 2016) immobilization of Zn(8)7-91%), Cd(70-83%), and Pb (33-50%) contaminated land (Wasilkowski et al, 2017). Fernández and Cordero, 2005 In addition, the application of an organic fertilizer based on coffee pulp improves the distribution of Trichoderma spp (T. koningii, T. harzidigestoanum and T. longibrachiatum) in soil.…”
Section: Uses 21 Uses In Agriculturementioning
confidence: 97%
“…Coffee pulp has been used to amend and improve soils by composting methods (Betancourt et al, 2016) and inoculating mycorrhizals (Osorio et al, 2002), management of soil treatment cycles (Pagan-Roig et al, 2016;Pagán-Roig et al, 2016) and phytoremediation (Wasilkowski et al, 2017). In these cases, increased growth (Senthilkumar et al, 2015), (Osorio et al, 2002) and production (Pagán-Roig et al, 2016), (Senthilkumar et al, 2015) of treated plants, increased biomass (Pagan-Roig et al, 2016;Pagán-Roig et al, 2016;Wasilkowski et al, 2017), increased humic acids and polymerization (Pagán-Roig et al, 2016) have been reported.…”
Section: Uses 21 Uses In Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…1), SS organic matter also has beneficial effects on many soil physical properties, including soil porosity and soil aggregation, and the increasing retention and movement of water (Kominko et al 2017). Furthermore, the increase of organic matter in SS-amended soils can reduce the bioavailability of HMs to plants due to the ability of metals to form stable complexes with organic matter (Park et al 2011;Wasilkowski et al 2017).…”
Section: The Ss Soil Application Improved the Physicochemical Propertmentioning
confidence: 99%